Efek Moderasi Manajemen Perubahan Dalam Pengaruh Kepemimpinan Transformasional Terhadap Budaya Organisasi - Basyari, Alif Sulthon; Dzulquarnain, Abi Hanif (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Background - Educational institutions, such as schools and universities, have a strategic role in shaping the character, intellectual abilities and skills of students to face future challenges. However, educational institutions also have to face complex challenges, such as social, technological and environmental changes that continue to develop. Therefore, educational institutions need to have an adaptive and innovative organizational culture. In this article, we will discuss the concept of organizational culture and its important role in creating a conducive work environment, as well as the factors that influence organizational culture in educational institutions. Aim - The purpose of this study was to examine the influence of transformational leadership on the dimensions of Dennison's organizational culture, namely work relations, employee involvement and satisfaction and change management as moderating variables and carried out at the Bina Insan Bangkalan Foundation as a research object. Desaign/ methodology/ approach - This research was conducted using a quantitative approach, which is a study that aims to test theory and examine causal relationships on research objects at the Bina Insan Foundation Educational Institution, so that it can produce a general conclusion. Research using a quantitative approach emphasizes data consisting of numbers, and can be analyzed. using statistical procedures with the SMART PLS data processing application system. Results and Discussion - Transformative leadership is still considered to be one of the most important things for the continuity of good performance and organizational culture at the Bina Insan Bangkalan Foundation. this is shown based on research results, how leadership influences significantly and positively towards the creation of a good Organizational Culture dimension, which includes employee involvement, employee satisfaction, and work relations. a leader who is considered good and able to accommodate the existing system at the Bina Insan Bangkalan Foundation is still the main axis for carrying out all existing activities. In addition, it is also based on research results that change which is a control variable actually weakens the relationship between transformational leadership and organizational culture that has been built. This means that for the current period, the Bina Insan Foundation still has not accepted any structured changes. Conclussion - The results showed that transformational leadership had a positive and significant effect on the Denison dimensions of Organizational Culture (change management, employee satisfaction, and involvement. However, change management weakened the relationship between transformational leadership variables on the Denison dimensions of organizational culture at the Bina Insan Bangkalan Foundation. Research Implication – This research can provide an overview of the independent variables from the Denison dimensions of organizational culture, one of which is transformational leadership and change management.